2019
DOI: 10.1111/hae.13905
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of changing from standard half‐life (SHL) to extended half‐life (EHL) FVIII prophylaxis on health‐related quality of life (HRQoL) in boys with moderate/severe haemophilia A: Lessons learned with the CHO‐KLAT tool

Abstract: Introduction: In many countries, there is a shift from standard half-life (SHL) to extended half-life (EHL) clotting factor concentrates (CFCs).Aim: To describe the experience of switching from SHL to an EHL FVIII CFC and the impact of this on frequency of infusions, factor consumption, bleeding rates and HRQoL using the Canadian Hemophilia Kids' Life Assessment Tool (CHO-KLAT).Methods: A retrospective chart review was conducted at a single haemophilia treatment centre in 2018 that included boys (ages: 4-18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
(17 reference statements)
1
15
1
Order By: Relevance
“…However, EHL utilization was estimated based on the initial prescribed EHL regimen, and the majority of data was derived from a single paediatric centre. Similarly, in a Canadian paediatric single‐centre retrospective study, Carcao and colleagues reported a 17% reduction in the median FVIII utilization following switching to rFVIIIFc, while maintaining a low stable ABR (1.2 vs. 1.0 pre‐ and post‐switch) 6 …”
Section: Discussionmentioning
confidence: 86%
“…However, EHL utilization was estimated based on the initial prescribed EHL regimen, and the majority of data was derived from a single paediatric centre. Similarly, in a Canadian paediatric single‐centre retrospective study, Carcao and colleagues reported a 17% reduction in the median FVIII utilization following switching to rFVIIIFc, while maintaining a low stable ABR (1.2 vs. 1.0 pre‐ and post‐switch) 6 …”
Section: Discussionmentioning
confidence: 86%
“…1,2 Several studies demonstrated a reduced infusion frequency, lower clotting factor consumption (CFC), and slightly lower annual bleeding rates (ABR). [3][4][5] The objective of this study was to evaluate the impact of switching from standard half-life (SHL) products to rFVIII-Fc (Efmoroctocog alfa, Elocta) and rFIX-Fc (Eftrenonacog alfa, Alprolix) on pharmacokinetics (PK), CFC, prophylactic infusion frequency, and ABR.…”
mentioning
confidence: 99%
“…In our experience, the CHO‐KLAT v2.0 was unable able to detect significant changes in HRQoL scores in groups of boys with hemophilia on long‐term prophylaxis who switched from a SHL to an EHL FC and who had very low spontaneous bleeding rates 20 . However, improvements in HRQoL have been reported using other HRQoL tools in populations of boys who switched from SHL to EHL FCs and who had high bleeding rates at the time of the switch in product 21 .…”
Section: Discussionmentioning
confidence: 73%
“…In our experience, the CHO-KLAT v2.0 was unable able to detect significant changes in HRQoL scores in groups of boys with hemophilia on long-term prophylaxis who switched from a SHL to an EHL FC and who had very low spontaneous bleeding rates. 20 However, improvements in HRQoL have been reported using other HRQoL tools in populations of boys who switched from SHL to EHL FCs and who had high bleeding rates at the time of the switch in product. 21 To the best of our knowledge, no existing disease-specific HRQoL tools have been able to demonstrate improvement in total scores TA B L E 4 Baseline scores with domain breakdown for matched pairs of child-parent scores and comparison between those using standard half-life (SHL)and extended half-life (EHL) clotting factor replacement therapies in the absence of high bleeding rates before the switch.…”
Section: New Questions Cmentioning
confidence: 99%